(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Central university libraries play a pivotal role in enhancing the quality of higher education by providing access to diverse resources, facilitating research, and fostering intellectual engagement. This paper aims to assess the multifaceted role of central university libraries in advancing higher education quality. Through a comprehensive review of literature, this paper examines the various functions and contributions of central university libraries, explores challenges faced, and identifies potential areas for improvement. Additionally, the paper discusses the evolving role of libraries in the digital age and highlights innovative strategies adopted by central university libraries to meet the changing needs of students, faculty, and researchers.